Electrodissection and classical tonsillectomy complications. Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2020)
Tonsillectomy is one of the most frequent surgical procedures in our times especially in pediatric age. In order to determine the complications of electrodissection and classical tonsillectomy in pediatric patients who were admitted at the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga in 2017, a review of 119 medical charts was performed. The results show that 73.95% of the cases had electrodissection tonsillectomy and 26.05% had classical tonsillectomy. The main indications for surgery were recurrent tonsillitis (electrodissection: 86.09% and classical: 80.65%) and tonsillar hypertrophy (electrodissection: 60.23% and classical: 35.48%). For both techniques, the mean surgical time was between 21-40 minutes (44.32% and 48.39%, respectively) and the hospital stay was less than one day (54.55% and 61.29%, each). The main intraoperative complication reported was hemorrhage (29.03% for classical versus 15.91% for electrodissection). Among the postoperative complications, pain (63.64%) and fever (60.23%) prevailed in patients with electrodissection tonsillectomy while fever was most frequent in patients with classical tonsillectomy (61.29%). These results show that both techniques have similar surgical time and hospital stay but differ in type of complications.
Keywords: tonsillectomy; classical technique; electrodissection; complications